Final technical report RUAF - from seed to table, 2009-2011 - Amerasinghe, Priyanie H.; Yadava, Chenna Basappa Gangappa; Wijenayake, K.M.A.; Suleman, K.B. (International Water Management Institute, 2011)
This is the final report (2009-2011 June) of the RUAF-FSTT Programme for the South and SOUTHEAST ASIA Region, coordinated by the International Water Management Institute (IWMI), from its Regional Office in Hyderabad, India. The programme of activities were carried out in two cities, namely Magadi, Ramanagara District, India, and Gampaha, Sri Lanka from 2009 to June 2011, with an no-cost extension of six months, ending in year June 2011. This programme of activities came under IWMI's theme on Water quality, Health and Environment. The programme was aimed at strengthening farmer organisations and their marketing capacities in urban/periurban settings, and developing sustainable urban farming systems that will contribute towards poverty alleviation, empowerment of disadvantaged and underserved groups in cities, enhance urban food security and social inclusion in development. The core activities were planned around two major components; 1. Operationalisation of a City Strategy Agenda (CSA), through a city multistakeholder forum (MSF) to promote Urban/Periurban Agriculture (UPA), which included diverse UPA activities and supported the shaping of policies to sustain UPA activities; 2. An innovation project that targeted low-income urban producers to innovate their farming practices from a market chain perspective, promoting eco-intensive agriculture based on ecological principals and maximum use of natural resources.